Narrative Communication in HIV/AIDS Education:The Impact of Storytelling on Health Behavior Change - RD.D.Lokita Pramesti; Poppie Indriyanti; Saktisyahputra Saktisyahputra (Journal of Public Health Indonesian, 2026)
Narrative communication and storytelling have increasingly been recognized as powerful tools in HIV/AIDS health education, offering culturally resonant pathways for promoting behavior change, reducing stigma, and improving health outcomes among diverse populations. This systematic literature review synthesizes evidence from 25 peer-reviewed studies published between 2021 and 2025, examining the mechanisms through which narrative formats — including oral and theatrical storytelling, digital storytelling, video-delivered serial dramas, mHealth narratives, and peer ambassador models — influence knowledge, attitudes, and practices related to HIV/AIDS prevention, testing, treatment adherence, and stigma reduction. Findings indicate that narrative interventions are consistently associated with increased HIV knowledge and awareness, reduced stigma and discrimination, improved HIV testing and screening uptake, enhanced antiretroviral therapy (ART) adherence, and decreased sexual risk behaviors. Theoretical frameworks including narrative persuasion theory, social cognitive theory, and the Health Belief Model provide robust explanatory foundations for the documented effects. Cultural adaptation, community participation, and digital media integration emerge as critical moderating factors that amplify narrative efficacy across diverse populations, including adolescents and young adults, people living with HIV (PLHIV), migrants and refugees, Black and other minority communities, and rural populations. The paper also identifies persistent barriers — including health literacy limitations, structural stigma, and implementation fidelity challenges — and proposes a research framework mapping the full pathway from theoretical foundations to measurable outcomes. These insights provide actionable guidance for public health practitioners, communication specialists, and policymakers designing HIV/AIDS education programs